Softcopy photogrammetry and lidar as sources for coastal morphommetric 3D surveys (tidal marshes and costal dunes): spatial analysis capabilities in a gis environment - Resumen Autores (Boletín de la Asociación de Geógrafos Españoles)
Resumen